DETERMINANT OF CAPITAL STRUCTURE ON MULTINATIONALITY COMPANY IN INDONESIA - Elok Faiqoh Himmah; Sedianingsih Sedianingsih (Universitas Jember, 2017)
This study aims to examine the factors that affect the capital structure. This research use independent variable that is multinational, managerial ownership, tax uncertainty, while the control variable is effective tax rate, profit growth, return on asset, firm size, current ratio, capital intensity, and inventory intensity. The population of this study consists of all non-financial companies listed on the Indonesia Stock Exchange from 2012-2016. The sample of this research is multinational company which means having subsidiaries outside Indonesia. Statistical method used in this research is multiple linear regression analysis. The results of this study indicate that multinationality, managerial ownership, and uncertainty tax have no significant effect on capital structure. while for control variable, return on asset and firm size that have significant influence to capital structure. Keywords: capital structure, multinational company, multiple regression